The Effectiveness of Flashcard Media as a Hijaiyah Script Learning Media at TPQ Shaqul Al Husna in Indonesia - Anisa Nur Utami; Aisyah; Farha Syarifuddin; Silfi Azaroh Fatla Humairoh; Syifa Nurnisa Sahidi; Tsamaroh Nafiah; Ahmad Nurrohim (Walidem Institute and Publishing (WIP), 2025)
Objective: To identify the effectiveness of flashcard media in increasing children's interest and motivation in knowing hijaiyah letters, especially at TPQ Shaqul Al Husna in Indonesia. Theoretical framework: Based on the Visual Learning Theory (Dual Coding Theory) and the Learning Motivation Theory (Self-Determination Theory), flashcards are seen as able to effectively combine visual and verbal information, while creating a fun learning experience. Literature Review: The use of flashcards has been proven to accelerate the mastery of hijaiyah letters by up to 80%, increase attention and retention in early childhood, and attract attention through interactive designs with colours and illustrations. Methods: Using a qualitative approach, data were collected through in-depth interviews with teachers and parents of students as well as literature reviews. Results: The results of the study showed that the use of card media (flashcards) succeeded in increasing children's interest and motivation in knowing hijaiyah letters. Interactive design with colors, illustrations, and relevant keywords helps children more easily recognize and remember hijaiyah letters. This approach creates a more fun and effective learning atmosphere than conventional methods. Implications: These findings are relevant to be applied in formal and non-formal education while offering a new approach to teaching hijaiyah letters that is more effective and fun. Novelty: This research contributes by Developing an interactive and specific flashcard design for learning hijaiyah letters.